2014
DOI: 10.1007/s10658-014-0509-3
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of Microdochium majus and Microdochium nivale associated with Fusarium head blight of wheat in Hokkaido, Japan

Abstract: Microdochium majus and Microdochium nivale are two of fungal pathogens that cause Fusarium head blight (FHB) in wheat, and have also caused pink snow mold in eastern Hokkaido, Japan. With the aim of assessing levels of genetic variation and population structure, 172 isolates of these Microdochium species obtained from five populations of infected wheat seeds were first classified into each species using polymerase chain reaction (PCR) amplification with specific primers. In total 165 (95.9 % of all isolates) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Glynn & S.G. Edwards (Glynn et al 2005 ; Watanabe et al 2011 ; Hayashi et al 2014 ). M. nivale and M. majus can be differentiated by morphological means (Gerlach and Nirenberg 1982 ; Lees et al 1995 ; Hernández-Restrepo et al 2016 ), quantitative real-time PCR (Nielsen et al 2013 ; Sonia et al 2018 ), molecular markers (Hayashi et al 2014 ; Matušinsky et al 2019 ), and gene-sequence analyses (Einax and Voigt 2003 ; Jewell and Hsiang 2013 ). Very recently, Abdelhalim et al ( 2020 ) demonstrated that M. nivale isolates revealed genetic differences related to different host plants (grasses vs .…”
Section: Taxonomy Host Range and Economic Importancementioning
confidence: 99%
“…Glynn & S.G. Edwards (Glynn et al 2005 ; Watanabe et al 2011 ; Hayashi et al 2014 ). M. nivale and M. majus can be differentiated by morphological means (Gerlach and Nirenberg 1982 ; Lees et al 1995 ; Hernández-Restrepo et al 2016 ), quantitative real-time PCR (Nielsen et al 2013 ; Sonia et al 2018 ), molecular markers (Hayashi et al 2014 ; Matušinsky et al 2019 ), and gene-sequence analyses (Einax and Voigt 2003 ; Jewell and Hsiang 2013 ). Very recently, Abdelhalim et al ( 2020 ) demonstrated that M. nivale isolates revealed genetic differences related to different host plants (grasses vs .…”
Section: Taxonomy Host Range and Economic Importancementioning
confidence: 99%
“…These fungi cause economic losses in wheat and barley ( Tronsmo et al, 2001 ; Abdallah-Nekache et al, 2019 ; Mao et al, 2023 ). These two agents also cause head blight, which is frequently observed in wheat ( Kammoun et al, 2009 ; Pancaldi et al, 2010 ; Hayashi et al, 2014 ). In a study conducted in Morocco, it was reported that wheat grains were highly contaminated with M. majus ( Saoudi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Irrespective of their original host, M. nivale sensu stricto and M. majus display differential virulence toward their hosts [52]. M. nivale sensu stricto (that is known to be characterized by high genetic diversity in contrast to M. majus [46,51]) was shown to have genetic differences related to different host plants (grasses and cereals) [25] and different turf grass species [53].…”
Section: Introductionmentioning
confidence: 99%